AN ANALYSIS OF TYPES OF DEIXIS IN THE SONG LYRICS OF 'GIVE ME YOUR FOREVER' BY ZACK TABUDLO - Mustafidah, Any Dinda Zahrotul; Putri, Aprilia Riyana (English Review: Journal of English Education, 2025)
This study aims to analyze the deixis used in the lyrics of the song "Give Me Your Forever" by Zack Tabudlo and examine its functions within the context of the song. Adopting a qualitative analysis approach, the research identifies various forms of deixis, including person, temporal, and spatial deixis. The analysis reveals that person deixis, through pronouns such as "I" and "you," plays a significant role in establishing relationships and emotional connections between the singer and the listener. Temporal deixis is explored through expressions referring to specific time frames, which anchor emotions and experiences within a particular context, enhancing the emotional depth of the song. Additionally, spatial deixis is examined through terms indicating location, which serve to enrich the meaning of the interactions depicted in the lyrics. The findings highlight how the use of deixis not only enhances the lyrical content but also creates emotional resonance for the listeners, demonstrating the complexity of communication in music through the interplay of language, time, space, and emotion.